SAT0429 How phenotype of the small fibre neuropathy (SFN) in primary sjÖgren syndrome (PSS) differs from others causes of small fibre neuropathy?. (12th June 2018) - Descamps, E.; Henry, J.; Labeyrie, C.; Adams, D.; Aiello, D.; Mariette, X.; Seror, R.
Abstract : Background: Small fibre neuropathy (SFN) is a peripheral neuropathy characterised by neuropathic pain associated with normal routine nerve conduction study but rarefaction of intraepidermal nerve fibres (IEFN). Primary Sjögren Syndrome (pSS) is one of the many etiology of SFN. Objectives: To compare phenotype of SFN in pSS, transthyretin (TTR) familial amyloidosis and idiopathic SFN. To describe evolution of SFN in pSS. Methods: All patients referred since October 2012 with a biopsy-proven SFN associated with either pSS (ACR/ EULAR 2016 criteria), TTR-amyloidosis or idiopathic were included in this monocentric retrospective study. Diagnosis of SFN was confirmed by normal nerve conduction study and abnormal lower limb skin biopsies. All patients undergo standardised diagnosis procedures during an outpatient day-clinic, pSS patients were further followed and undergo a second evaluation. Characteristics of SFN were compared between 3 groups: pSS, TTR-amyloidosis and idiopathic, and outcome of pSS associated SFN was analysed. Results: We included 15 patients with pSS (13 (86.7%) women, median age: 56 years [IQR:46.5–63.5], 7 (46.7%) anti-SSA positive, 12 (80%) focus score ≥1), 17 with TTR-amyloidosis (7 (41.2%) women, median age: 47 years 35–56 ) and 11 with idiopathic SFN (7 (63.6%) women, median age: 47 years [36–56.5]). Patients with pSS had a median ESSDAI of 5. 5–8 One had monoclonal gammopathy, 5/13 (38.5%) rheumatoid factor, 2/13 (15.4%) hypergammaglobulinemia and none had cryoglobulin. Time from first neurologic symptoms to diagnosis of SFN was significantly higher for pSS (29 months [8.5–65]) and idiopathic group (35 months [11.5–65]) than for TTR group (6 months [0–15]). Clinical presentation was length dependant in only 2 (13.3%) patients with pSS compared to 10 (58.8%) in TTR amyloidosis (p=0.01) and 2 (18.2%) in idiopathic group (p=1). A "patchy" presentation (defined by asymmetrical and/or proximal symptoms involving limb, trunk and/or face), was significantly more frequent in pSS than in TTR amyloidosis (7 (43.7%) vs. 1 (5.9%); p=0.01). This more frequent non-length dependant course was confirmed on skin biopsies with an IEFN at proximal site <IEFN at distal site in 7/14 (50%) pSS patients compared to 2/15 (13.3%) in TTR (p=0.05) and 1 (9.1%) in idiopathic (p=0.04) groups. Lauria score was significantly higher in pSS than in TTR, (5 [4–7.5] vs. 2, 2–5 p=0.007), mainly due to items of sicca symptoms (n=14/15) and peripheral limb pain (n=13/15). Ten patients with pSS have been reassessed with a median follow up of 31 months [16.5–53.5]. At reassessment, the Lauria score did not significantly differ (6 5–7 ) from initial score, patchy presentation was still predominant 5 (50%). Patients did not evolve through large fibre neuropathy, except one patient who had received a neurotoxic chemotherapy by platin for ovarian cancer, between the 2 evaluations. Conclusions: pSS patients with SFN had a low frequency of serum B cell activation biomarkers. Compared to other causes of SFN, in pSS SNF was characterised by a more frequent non-length dependant and patchy presentation and a higher Lauria score. After a median follow-up of 31 months, SFN in pSS were stable in the time and did not evolve through large fibre neuropathy. Disclosure of Interest: None declared